The Effectiveness of Sajojo Dance on Anxiety and Stress in Adolescent in Papua - Yustika Rahmawati Pratami; Harlinda Widya Putri; Nurhilmi Nurhilmi (Indonesian Journal of Global Health Research, 2025)
This research is a 2024 Kemendikbudristek Grant research which is a form of development of non-pharmacological and cost-effective interventions selected based on scientific research that have benefits for adolescents in reducing stress and anxiety that are safe and enjoyable. The aims to determine whether the sajojo dance as a typical Papuan dance is effective in reducing anxiety and stress in adolescents. Method: this study is a true experimental with a pretest-posttest control group design and uses proportional random sampling techniques. The population in this study was 40 students. This study found that there was no significant change in the control group because it was accompanied by an increase in anxiety and stress in adolescents and there was a significant change in the intervention group related to reducing anxiety and stress. Sajojo dance is effective as a non-pharmacological treatment in reducing anxiety and stress in adolescents.